CHARACTERISTIC OF THE MECHANISMS FOR PROVIDING THE EXECUTIVE DISCIPLINE IN THE BODIES OF THE PUBLIC SERVICE - Yashutin, Igor (Public Administration and Regional Development, 2022)
In the article, the author characterizes the mechanisms for ensuring executive discipline in public service bodies. Attention is focused on the need to introduce the best trends of foreign experience into the domestic practice of public administration, as well as a cross-cutting revision of the basic mechanisms for ensuring executive discipline in public service bodies, taking into account the changes that have occurred in the public life of Ukraine and the current legislation regulating the activities of civil servants. The author of the article pays special attention to the basic mechanisms for ensuring executive discipline in public service bodies in order to radically update them, in particular, such as regulatory, organizational, planning, control, assessment and quality management. In addition, he proposes to expand the classification of basic mechanisms for ensuring performing discipline in public service bodies, thanks to the transformation processes of Ukraine into a European simple, the study and generalization of the best experience of foreign countries in this area of activity - modern, new, which include motivational-value, crowdsourcing, crowdfunding, etc. This will help to strengthen and develop in the future the level of executive discipline of civil servants and local government officials in the public service through self-improvement, self-development and self-realization of their abilities. Draws attention to an integrated approach to solving the problem of choosing innovative mechanisms for ensuring performing discipline in public service bodies. The expediency of studying the characteristics of the mechanisms for ensuring executive discipline in public service bodies is determined by the importance of developing good democratic governance in Ukraine, highlighting innovative mechanisms for improving executive discipline in public service bodies at a multi-level public administration. This will help to improve the reputation of the public service in the authorities, to enhance the image of a public servant, and to form a qualitatively new system of public service in Ukraine.